NEW
New Website Launch
Experience the best way to solve previous year questions with mock tests (very detailed analysis), bookmark your favourite questions, practice etc...
1

JEE Advanced 2015 Paper 2 Offline

MCQ (More than One Correct Answer)
Let $$F:R \to R$$ be a thrice differentiable function. Suppose that
$$F\left( 1 \right) = 0,F\left( 3 \right) = - 4$$ and $$F\left( x \right) < 0$$ for all $$x \in \left( {{1 \over 2},3} \right).$$ Let $$f\left( x \right) = xF\left( x \right)$$ for all $$x \in R.$$

The correct statement(s) is (are)

A
$$f'\left( 1 \right) < 0$$
B
$$f\left( 2 \right) < 0$$
C
$$f'\left( x \right) \ne 0$$ for any $$x \in \left( {1,3} \right)$$
D
$$f'\left( x \right) = 0$$ for some $$x \in \left( {1,3} \right)$$

Explanation

Given,

F(1) = 0, F(3) = 4

F'(x) < 0 for all x $$\in$$(1, 3)

and f(x) = xF(x)

Now, f'(x) = F(x) + xF'(x)

$$\Rightarrow$$ f'(1) = F(1) + 1 . F'(1)

$$\Rightarrow$$ f'(1) = 0 + F'(1) ....... (1)

As F'(x) < 0 for all x $$\in$$ (1, 3)

$$\therefore$$ F'(1) < 0

From (1), we get

f'(1) = F'(1) < 0

From Lagrange theorem

$$F'(2) = {{F(3) - F(1)} \over {3 - 1}}$$

$$ = {{ - 4 - 0} \over 2}$$

= $$-$$2

As f(x) = xF(x)

$$\therefore$$ f(3) = 3 . F(3) = 3 . ($$-$$4) = $$-$$12

and f(1) = 1 . F(1) = 0

$$\therefore$$ $$f'(2) = {{f(3) - f(1)} \over {3 - 1}}$$

$$ = {{ - 12} \over 2} = - 6$$

As, f'(x) = F(x) + x . F'(x)

$$\therefore$$ f'(2) = F(2) + 2 . F'(2)

$$ \Rightarrow - 6 = {{f(2)} \over 2} + 2.\,( - 2)$$

$$ \Rightarrow {{f(2)} \over 2} = - 2$$

$$\Rightarrow$$ f(2) = $$-$$4

$$\therefore$$ f(2) < 0

$$f'(x) = {{f(3) - f(1)} \over {3 - 1}}$$ when x $$\in$$ (1, 3)

f(3) = $$-$$12

and f(1) = 0

$$\therefore$$ $$f'(x) = {{ - 12} \over 2} = - 6$$

$$\therefore$$ f'(x) $$\ne$$ 0 for any x $$\in$$(1, 3)

2

JEE Advanced 2015 Paper 2 Offline

MCQ (More than One Correct Answer)
Let $$F:R \to R$$ be a thrice differentiable function. Suppose that
$$F\left( 1 \right) = 0,F\left( 3 \right) = - 4$$ and $$F\left( x \right) < 0$$ for all $$x \in \left( {{1 \over 2},3} \right).$$ Let $$f\left( x \right) = xF\left( x \right)$$ for all $$x \in R.$$

If $$\int_1^3 {{x^2}F'\left( x \right)dx = - 12} $$ and $$\int_1^3 {{x^3}F''\left( x \right)dx = 40,} $$ then the correct expression(s) is (are)

A
$$9f'\left( 3 \right) + f'\left( 1 \right) - 32 = 0$$
B
$$\int_1^3 {f\left( x \right)dx = 12} $$
C
$$9f'\left( 3 \right) - f'\left( 1 \right) + 32 = 0$$
D
$$\int_1^3 {f\left( x \right)dx = -12} $$

Explanation

Given, $$\int_1^3 {{x^2}F'(x)dx = - 12} $$

$$ \Rightarrow [{x^2}F(x)]_1^3 - \int_1^3 {2x\,.\,F(x)dx = - 12} $$

$$ \Rightarrow 9F(3) - F(1) - 2\int_1^3 {f(x)dx = - 12} $$

[$$\because$$ $$xF(x) = f(x)$$ given]

$$ \Rightarrow - 36 - 0 - 2\int_1^3 {f(x)dx = - 12} $$

$$\therefore$$ $$\int_1^3 {f(x)dx = - 12} $$

and $$\int_1^3 {{x^3}F''(x)dx = 40} $$

$$ \Rightarrow [{x^3}F'(x)]_1^3 - \int_1^3 {3{x^2}F'(x)dx = 40} $$

$$ \Rightarrow [{x^2}(xF'(x)]_1^3 - 3 \times ( - 12) = 40$$

$$ \Rightarrow \{ {x^2}\,.\,[f'(x) - F(x)]\} _1^3 = 4$$

$$ \Rightarrow 9[f'(3) - F(3)] - [f'(1) - F(1)] = 4$$

$$ \Rightarrow 9[f'(3) + 4] - [f'(1) - 0] = 4$$

$$ \Rightarrow 9f'(3) - f'(1) = - 32$$

3

JEE Advanced 2015 Paper 2 Offline

MCQ (More than One Correct Answer)
The option(s) with the values of a and $$L$$ that satisfy the following equation is (are) $$${{\int\limits_0^{4\pi } {{e^t}\left( {{{\sin }^6}at + {{\cos }^4}at} \right)dt} } \over {\int\limits_0^\pi {{e^t}\left( {{{\sin }^6}at + {{\cos }^4}at} \right)dt} }} = L?$$$
A
$$a = 2,L = {{{e^{4\pi }} - 1} \over {{e^\pi } - 1}}$$
B
$$a = 2,L = {{{e^{4\pi }} + 1} \over {{e^\pi } + 1}}$$
C
$$a = 4,L = {{{e^{4\pi }} - 1} \over {{e^\pi } - 1}}$$
D
$$a = 4,L = {{{e^{4\pi }} + 1} \over {{e^\pi } + 1}}$$

Explanation

Let $${I_1} = \int_0^{4\pi } {{e^t}({{\sin }^6}at + {{\cos }^6}at)dt} $$

$$ = \int_0^\pi {{e^t}({{\sin }^6}at + {{\cos }^6}at)dt + \int_\pi ^{2\pi } {{e^t}({{\sin }^6}at + {{\cos }^6}at)dt + \int_{2\pi }^{3\pi } {{e^t}({{\sin }^6}at + {{\cos }^6}at)dt + \int_{3\pi }^{4\pi } {{e^t}({{\sin }^6}at + {{\cos }^6}at)dt} } } } $$

$$\therefore$$ $${I_1} = {I_2} + {I_3} + {I_4} + {I_5}$$ ...... (i)

Now, $${I_3} = \int_\pi ^{2\pi } {{e^t}({{\sin }^6}at + {{\cos }^6}at)dt} $$

Put $$t = \pi + t \Rightarrow dt = dt$$

$$\therefore$$ $${I_3} = \int_0^\pi {{e^{\pi + t}}.\,({{\sin }^6}at + {{\cos }^6}at)dt} $$

$$ = {e^t}\,.\,{I_2}$$ ..... (ii)

Now, $${I_4} = \int_{2\pi }^{3\pi } {{e^t}({{\sin }^6}at + {{\cos }^6}at)dt} $$

Put $$t = 2\pi + t \Rightarrow dt = dt$$

$$\therefore$$ $${I_4} = \int_0^\pi {{e^{t + 2\pi }}({{\sin }^6}at + {{\cos }^6}at)dt} $$

$$ = {e^{2\pi }}.{I_2}$$ ...... (iii)

and $${I_5} = \int_{3\pi }^{4\pi } {{e^t}({{\sin }^6}at + {{\cos }^6}at)dt} $$

Put $$t = 3\pi + t$$

$$\therefore$$ $${I_5} = \int_0^\pi {{e^{3\pi + t}}({{\sin }^6}at + {{\cos }^6}at)dt} $$

$$ = {e^{3\pi }}.\,{I_2}$$ ...... (iv)

From Eqs. (i), (ii), (iii) and (iv), we get

$${I_1} = {I_2} + {e^\pi }.\,{I_2} + {e^{2\pi }}.\,{I_2} + {e^{3\pi }}.\,{I_2}$$

$$ = (1 + {e^\pi } + {e^{2\pi }} + {e^{3\pi }}){I_2}$$

$$\therefore$$ $$L = {{\int_0^{4\pi } {{e^t}({{\sin }^6}at + {{\cos }^6}at)dt} } \over {\int_0^\pi {{e^t}({{\sin }^6}at + {{\cos }^6}at)dt} }}$$

$$ = (1 + {e^\pi } + {e^{2\pi }} + {e^{3\pi }})$$

$$ = {{1.\,({e^{4\pi }} - 1)} \over {{e^\pi } - 1}}$$ for $$a \in R$$

4

JEE Advanced 2015 Paper 2 Offline

MCQ (More than One Correct Answer)
Let $$f\left( x \right) = 7{\tan ^8}x + 7{\tan ^6}x - 3{\tan ^4}x - 3{\tan ^2}x$$ for all $$x \in \left( { - {\pi \over 2},{\pi \over 2}} \right).$$
Then the correct expression(s) is (are)
A
$$\int\limits_0^{\pi /4} {xf\left( x \right)dx = {1 \over {12}}} $$
B
$$\int\limits_0^{\pi /4} {f\left( x \right)dx = 0} $$
C
$$\int\limits_0^{\pi /4} {xf\left( x \right)dx = {1 \over {6}}} $$
D
$$\int\limits_0^{\pi /4} {f\left( x \right)dx = 1} $$

Explanation

$$f(x) = 7{\tan ^8}x + 7{\tan ^6}x - 3{\tan ^4}x - 3{\tan ^2}x\,\forall x \in \left( {{{ - \pi } \over 2},{\pi \over 2}} \right)$$

$$ = 7{\tan ^6}x\,.\,{\sec ^2}x - 3{\tan ^2}x\,.\,{\sec ^2}x$$

$$ = (7{\tan ^6}x - 3{\tan ^2}x)\,.\,{\sec ^2}x$$

$$ \Rightarrow \int\limits_0^{\pi /4} {f(x)dx = \int\limits_0^{\pi /4} {(7{{\tan }^6}x - 3{{\tan }^2}x){{\sec }^2}dx = \int\limits_0^1 {(7 + 603{t^2})dt = [{t^7} - {t^3}]_0^1 = 0} } } $$

Also, $$I = \int\limits_0^{\pi /4} {xf(x)dx} $$

$$ = \left| {x\,.\,\int {(7{{\tan }^6}x - 3{{\tan }^2}x){{\sec }^2}xdx} } \right|_0^{\pi /4} - \int\limits_0^{\pi /4} {1\,.\,\int {(7{{\tan }^6}x - 3{{\tan }^2}x){{\sec }^2}x\,dx} } $$

$$ = \left| {x\,.\,({{\tan }^7}x - {{\tan }^3}x} \right|_0^{\pi /4} - \int\limits_0^{\pi /4} {({{\tan }^7}x - {{\tan }^3}x)dx} $$

$$ = 0 - \int\limits_0^{\pi /4} {{{\tan }^3}x({{\tan }^4}x - 1)dx} $$

$$ = - \int\limits_0^{\pi /4} {{{\tan }^3}x({{\tan }^2}x - 1)({{\sec }^2}x)dx} $$

$$ = - \int\limits_0^1 {({t^5} - {t^3})dt} $$

$$ = - \left[ {{{{t^6}} \over 6} - {{{t^4}} \over 4}} \right]_0^1 = \left[ {{1 \over 4} - {1 \over 6}} \right] = {1 \over {12}}$$

Joint Entrance Examination

JEE Main JEE Advanced WB JEE

Graduate Aptitude Test in Engineering

GATE CSE GATE ECE GATE EE GATE ME GATE CE GATE PI GATE IN

Medical

NEET

CBSE

Class 12